Liability for defects in sale of things with digital elements - Nikšić Saša (Anali Pravnog Fakulteta u Beogradu)
This paper presents the issue of liability for material defects in relation to things with digital elements. Croatian law was recently amended in this field as a consequence of implementation of the Directive (EU) 2019/771, and this paper compares the provisions of EU law with the Croatian law and the legal systems of some other EU member states. The focus of the paper is liability for material defects of things with digital elements, and consequently, the notion of things with digital elements is analyzed along with provisions on defects of such things, updates of things with digital elements, and defects in contracts for the continuous supply of digital content and digital services.